Handbook of Human Centric Visualization - Huang, Weidong; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Visualizations are visual representations of non-visual data. They are produced for people to interact with and to make sense of the underlying data. Rapid advances in display technology and computer power have enabled researchers to produce visually appealing pictures. However, the effectiveness of those pictures in conveying the embedded information to end users has not been fully explored. Handbook of Human Centric Visualization addresses issues related to design, evaluation and application of visualizations. Topics include visualization theories, design principles, evaluation methods and metrics, human factors, interaction methods and case studies. This cutting-edge book includes contributions from well-established researchers worldwide, from diverse disciplines including psychology, visualization and human-computer interaction. This handbook is designed for a professional audience composed of practitioners, lecturers and researchers working in the field of computer graphics, visualization, human-computer interaction and psychology. Undergraduate and postgraduate students in science and engineering focused on this topic will also find this book useful as a comprehensive textbook or reference.
Visual communication -- Theory and science -- Principles, guidelines and recommendations -- Methods -- Perception and cognition -- Dynamic visualization -- Interaction.
Keywords: Computer science; Artificial intelligence; Computer graphics; Visualization; Computer Science; User Interfaces and Human Computer Interaction; Visualization; Computer Graphics; Models and Principles; Artificial Intelligence (incl. Robotics).